Association of the protective effect of telmisartan on hearing loss among patients with hypertension - Cha, Jung-Joon; Yum, Yunjin; Kim, Yong Hyun; Kim, Eung Ju; Rah, Yoon Chan; Park, Euyhyun; Im, Gi Jung; Song, Jae-Jun; Chae, Sung-Won; Choi, June; Joo, Hyung Joon (Frontiers in Neurology, 2024)
Aim Hearing loss, affecting a significant portion of the global population, is prevented with peroxisome proliferator-activated receptor γ agonism. Understanding potential protective treatments is crucial for public health. We examine the effect of telmisartan, an antihypertensive drug and partial peroxisome proliferator-activated receptor γ agonist, on hearing loss in patients with hypertension.This retrospective cohort analysis used data from the OMOP Common Data Model database, encompassing information from three tertiary institutions in South Korea. The study included a substantial sample size of 860,103 people diagnosed with hypertension. The study included individuals who had been medically diagnosed with hypertension and had been prescribed antihypertensive drugs, including telmisartan. The study design was established to evaluate the comparative effects of telmisartan and other hypertension medications on hearing loss. We used propensity score matching (PSM) to create a balanced cohort, reducing potential biases between the telmisartan and non-telmisartan groups. From the initial 860,103 patients with hypertension, a propensity score matched cohort was derived from 20,010 patients, with 2,193 in the telmisartan group. After PSM, lower incidence of total hearing loss was observed in the telmisartan group compared to the non-telmisartan group during the 3-year follow-up (0.5% vs. 1.5%, log-rank p=0.005). In subgroup analysis, this study showed consistent results that lower incidence of total hearing loss was higher in the telmisartan group than in the non-telmisartan group. Telmisartan was associated with reducing certain types of hearing loss in patients with hypertension. Further research is needed to confirm these findings and understand the mechanisms.